The AGE Effect on Protective Behaviors During the COVID-19 Outbreak: Sociodemographic, Perceptions and Psychological Accounts - Pasion, Rita; Paiva, Tiago O.; Fernandes, Carina; Barbosa, Fernando (Frontiers in Psychology, 2020)
COVID-19 outbreak is a sudden and devastating global pandemic in which the control of the spread is highly dependent on individual reactions, until the development of a vaccine and adequate treatments. Considering that older adults are at high risk for COVID-related medical complications and mortality, the present study focuses on the age-related differences on the adoption of protective behaviors during the initial stages of this outbreak, while accounting for the role of sociodemographic, COVID-related, perceived risk, and psychosocial variables (i.e., anxiety, optimism, fear of death, and social isolation) in this relation. The study sample included 1696 participants, aged between 18-85 years old, who completed an online survey during the initial stages of the first COVID-19 outbreak in Portugal. Overall, results reveal that the engagement in protective behaviors declines with advancing age and that older adults show a pattern towards the lower perceived risk compared with middle-aged adults. Multicategorical mediation analyses show that anxiety, optimism, fear of death, and social isolation significantly mediate age effects on protective behaviors. Specifically, both anxiety and fear of death increase protective behaviors via higher perceived risk in the middle-aged and in the younger groups, respectively. Optimism directly predicts protective behaviors in the middle-aged groups, while social isolation reduces protective behaviors in the younger and older-aged groups. Results are discussed in terms of its implications for public health policies.